Application of power grid wind monitoring data in transmission line accident warning and handling affected by typhoon. (November 2022) - Zhang, Yi; Wu, Yifeng; Zhang, Feng; Yao, Xudong; Liu, Ang; Tang, Lv; Mo, Jianguo
Abstract: With the increasing number of transmission line monitoring points, it is possible to obtain meteorological monitoring data of power grid, and the meteorological monitoring data of power grid can be further used to guide typhoon disaster early prevention, fault repair and disposal of transmission faults. This paper innovatively proposes a typhoon microscale (100 m) wind field simulation method suitable for the complex terrain conditions in different coastal areas of China, and uses the power grid meteorological monitoring data to improve the early warning accuracy and credibility in the local terrain space of typhoon disasters. The prediction robustness and accuracy of the scale reduction prediction model are improved through continuous observation and statistical correction, several engineering examples show that the method is correct and effective. The dynamic typhoon prevention strategy of the power grid and the timely adjustment of the power grid operation mode can be guided for the preliminary analysis of the cause of the transmission failure after the typhoon transit, so as to provide scientific guidance for the subsequent emergency repair. This method has a general practical and guiding value for the coastal power grid of the typhoon influence area.